Frugal innovation for sustainable rural development - Mokter, Hossain (2023)
Sustainable development (SD) is a key concern for businesses, governments, and policymakers, with a particular emphasis on rural areas for achieving the sustainable development goals (SDGs). Frugal innovation offers a new and promising approach for sustainable rural development, but its specific contributions in this context remain underexplored in the existing literature. This study, therefore, aims to address this gap by examining how frugal innovation can contribute to sustainable development in rural areas. Using a grounded theory method and based on 22 interviews with key informants related to 13 cases of frugal enterprise in South Asia, this qualitative study attempts to accomplish the aim of the study. We developed a classification that identifies the increasing positive and decreasing negative parameters of SDGs to assess the extent to which frugal enterprises contribute to specific SDGs. Our findings show that frugal innovations tend to contribute more to SDGs than conventional products. However, certain SDGs have limited potential for frugal or other types of innovation to make significant contributions, as these goals are mainly intended to be assessed at the national level. Based on our findings, we discuss the implications and suggest future research avenues.